PENGARUH STRATEGI PEMBELAJARAN KONTEKSTUAL TERHADAP HASIL BELAJAR MATEMATIKA - Wahyu Budiono (Universitas PGRI Adi Buana Surabaya, 2015)
One of the problems in the mathematical learning in junior high was the low ability students in solving math problems that are packed in the form of a question which more emphasis on understanding and mastery of a particular subject matter. Addressing it, solutions that can be used through Contexstual approach to teaching and learning, in order to improve the understanding of students about the concept of comparison and scale, involve students actively in the learning, and encourages independent learning-centered students so teachers only as a facilitator. The problem in this research is whether there is a difference of material studied mathematics results comparison and scale between students who use contextual learning model and conventional learning model in Class VII SMPN 1 Sukodono. Therefore, this research aims to find out whether there are differences in the results of mathematical learning material and scale of comparison between students who use contextual learning model and conventional learning model in Class VII SMPN 1 Sukodono.The methods used in this research is a method of tests given to students in order to know the influence of student learning outcomes. The population in this research is grade VII SMPN 1 Sukodono school year 2014-2015. In this study, the authors take samples with the technique of non-random sampling that is Purposive sampling, Sample research this is a Class VII J SMPN Sukodono academic year 2014-2015 as the class exsperiment and Class VII J SMPN 1 Sukodono academic year 2014-2015 as the class of the control. The research data was collected using the engineering test. In this study the author uses test-t.From the results of research that has been carried out, then it can be drawn the conclusion that